P024 Effects of anti-TNF and anti-interleukins 12 and 23 drugs on circulating dendritic cells migratory capacity in inflammatory bowel disease. (30th January 2023) - Soleto, I; Ramirez, C; Gómez, C; Montse, B; García, S; Orejudo, M; Mecado, J; Chaparro, M; Gisbert, J P
Abstract: Background: Inflammatory bowel disease (IBD) is an idiopathic and chronic disorder that includes ulcerative colitis (UC) and Crohn's disease (CD). Both diseases are different but show an uncontrolled intestinal immune response that generates tissue inflammation. Dendritic cells (DC) are phagocytic professional antigen presenting cells that link the innate and adaptive immune systems. Indeed, they are the only cell type able to stimulate naïve T cells generating an antigen-specific immune response. In humans, DC can be divided into plasmacytoid (pDC) and c conventional type 1 and 2 (cDC1, cDC2). Although cDC migration towards the GI mucosa is enhanced in IBD, the mechanisms underlying these migrations and whether biological drugs can modulate them are currently unknown. This study aimed to analyze DC migratory capacity towards the GI mucosa, and whether biological drugs with different mechanisms of action can modulate this process in health and IBD. Methods: This is a cross-sectional observational postmarketing study where the modulatory effect of different biological treatments on samples from patients with an endoscopic diagnosis of IBD and healthy controls was studied ex vivo . Peripheral blood mononuclear cells (PBMC) were obtained from 15 patients per group and were cultured in presence of golimumab or ustekinumab. Following culture, surface markers expression was determined, assessing the differential effect of biological drugs (if any) over the DC subsets in the different groups. After that, the migratory capacity of circulating DC towards CCL2, CCL25, and MadCam1 from the different study groups was determined. Finally, we evaluated the DC migratory capacities in presence of biological drugs or with culture media alone. Results: The cCD2 subset showed higher expression levels of β7 and CCR5 compared to cCD1 (Figure 1). Golimumab and ustekinumab did not modify the expression of the homing markers in any studied subset (Figure 2). Even though no conclusive results were obtained for the biological drugs used in the study on the expression of homing markers, ustekinumab decreased the migratory capacity of cDC2 from CD patients towards a medium supplemented with CCL25 (Figure 3). Conclusion: cDC2 showed more migratory profile markers than other DC populations. Golimumab and ustekinumab did not modify the expression of the homing markers in any DC subset in any group. Nevertheless, ustekinumab decreased the migratory capacity of cDC2 from CD patients. This fact indicates that the behavior of this population is different in CD and UC and that the migration capacity of this subset is not dependent on homing markers.